Lecturers’ Professional Readiness for the Use of AI: An Analysis of Students’ Perceptions - Pirtskhalaishvili, Dea; Kharadze, Natalia (Sustainable Governance in the Age of Artificial Intelligence: Interdisciplinary Perspectives on ESG, Digital Transformation and Corporate Responsibility, 2026)
The need for AI integration in higher education is growing. It is worth noting that, along with regulations and a systematic approach, the lecturer plays a fundamentally important role, as the student interacts with the lecturer on a daily basis. As part of the research, we analyzed students' perceptions of lecturers' attitudes and professional readiness towards artificial intelligence. The study was conducted at Ivane Javakhishvili Tbilisi State University, in which 791 students participated. The SPSS statistical software package was used to analyze the obtained results. The article presents hypotheses and develops relevant recommendations. According to some students, lecturers' attitude towards artificial intelligence is negative. Furthermore, they believe that lecturers' fear or distrust of AI somewhat limits students. The research identified challenges that can be eliminated by raising the awareness of professors and forming a unified system.